Ethnic identity and inequalities in Britain : the dynamics of diversity / edited by Stephen Jivraj and Ludi Simpson. - Jivraj, Stephen; Simpson, Ludi, 1953- (Policy Press, 2015)
This important book is the first to offer an in-depth analysis from the last three UK population censuses, focusing on the dynamics of ethnic identity and inequalities in contemporary Britain, with contributions from experts based at or affiliated to the Centre on Dynamics of Ethnicity.